ANALISIS PERAN UNIT PENYELENGGARA BANDAR UDARA (UPBU) TERHADAP PENGAWASAN KESELAMATAN PENERBANGAN DI BANDAR UDARA H. HASAN AROEBOESMAN ENDE NUSA TENGGARA TIMUR - Risky Sulung; Rosiana Ulfa (Pusat Riset dan Inovasi Nasional, 2022)
Lately, there have been many airplane accidents in Indonesia, both casualties and no casualties, in Law No. 1 of 2009 concerning Aviation, aviation safety is matters related to aviation security and safety, accident investigations. aviation and the prevention of aviation accidents through the making of laws and regulations, education and training, also in the context of campaigns to inform the public on matters relating to air travel safety, as for the formulation of the problem as follows, what is the role and what are the obstacles to Safety Supervision in Department of Engineering, Operations, Security Emergency Services at (UPBU) H. Hasan Aroeboesman Ende East Nusa Tenggara. This study uses qualitative methods, data collection is carried out by interview methods, namely by interviewing the head of the TOKPD, Avsec commanders and AMC officers, observation by observing the flight safety supervision process by TOKPD, documentation by obtaining data on archive records and pictures, which is then carried out data analysis using data reduction, data display and conclusion/verification. The results of this study indicate that the implementation of operations under the head of TOKPD (Technical Operations, Security and Emergency Services), has an important role, namely Building Platform (banglan), Airport Electrical Engineering, Elban, PKP-PK and Avsec, for the implementation of maintenance for each unit. using daily, monthly, quarterly. Barriers to safety supervision by the Engineering, Operations, Security and Emergency Services sections, namely the covid-19 inspection which is not Avsec's responsibility, no Regulated Agent, there is no X-Ray Cargo, the X-ray machine for Baggage is damaged, from the personnel there are obstacles because indeed there are personnel who have attended the training but in the implementation in the field it may also not be carried out according to the applicable sop.